KERAS DEEP LEARNING PACKAGE IN PYTHON: A REVIEW - Dalia Shihab Ahmed; Rasha shaker ibrahim Al-badri; Firas Ali Hashim; Nadia Mahmood Hussien (Journal Park Publishing, 2023)
Python's popularity is growing. It is a member of the languages that are used most frequently, having supplanted a lot of others in the in the workplace. Python is well-known among developers for a lot of reasons, one of which is because it offers an exceptionally wide groups of libraries that people can utilize. This document gives an up-to-date assessment of Keras, an Application Programming Interface (API) for deep learning built on the Tensor Flow machine learning framework and developed using Python. The mentioned package utilizes Tensor Flow, and others, to integrate deep learning models such as neural network graphs for identifying medical problems, and others. The purpose of this paper is to guide readers to Keras, a library which offers exceptionally strong and abstract building blocks for deep learning networks.
Keywords: Keras, PyTorch, Tensor Flow, CNN, neural network graphs, Deep learning.